2017
DOI: 10.11005/jbm.2017.24.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Association between Sarcopenic Obesity and Metabolic Syndrome in Postmenopausal Women: A Cross-sectional Study Based on the Korean National Health and Nutritional Examination Surveys from 2008 to 2011

Abstract: BackgroundMenopause contributes to an increase in visceral fat mass and a decrease in muscle protein synthesis. Therefore, we performed this study to examine their relationship how effect the changes of body composition as obesity and sarcopenia on metabolic syndrome (MS) as a predictor of cardiovascular disease in postmenopausal women.MethodsUsing data from the Korean National Health and Nutrition Examination Survey (KNHANES) from 2008 to 2011, we estimated that 4,183 postmenopausal women underwent dual energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 22 publications
4
47
0
Order By: Relevance
“…Most clinical studies have reported that sarcopenic obesity is associated with metabolic syndrome [136][137][138]. However, in an Australian study assessing older men, sarcopenic obesity was associated with metabolic syndrome; however, obesity itself, rather than the sarcopenia measured by ALM, grip strength, or gait speed was more predictive of metabolic syndrome [139].…”
Section: Metabolic Syndromementioning
confidence: 87%
“…Most clinical studies have reported that sarcopenic obesity is associated with metabolic syndrome [136][137][138]. However, in an Australian study assessing older men, sarcopenic obesity was associated with metabolic syndrome; however, obesity itself, rather than the sarcopenia measured by ALM, grip strength, or gait speed was more predictive of metabolic syndrome [139].…”
Section: Metabolic Syndromementioning
confidence: 87%
“…Sarcopenia has been predictive of higher mortality in many cancers, including CRC, as was observed in our recent study. 23 Sarcopenia also has been related to higher systemic inflammatory response, 16,19,34 metabolic dysregulation, [38][39][40] and postsurgical complications, 14 and the effects of each of these muscle abnormalities appear to be independent predictors of outcomes in patients with CRC.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have been carried out in this field and with contradictory results. Cross‐sectional studies in sarcopenic obesity subjects have reported higher prevalence of cardiovascular risk factors and metabolic syndrome in those individuals . Strong associations with inflammatory markers compared with sarcopenia‐only subjects have been found .…”
Section: Introductionmentioning
confidence: 98%
“…Cross-sectional studies in sarcopenic obesity subjects have reported higher prevalence of cardiovascular risk factors and metabolic syndrome in those individuals. 6,7 Strong associations with inflammatory markers compared with sarcopenia-only subjects have been found. 8 Conversely, some longitudinal studies have shown that sarcopenic obesity does apparently not confer any greater mortality risk than sarcopenia alone.…”
Section: Introductionmentioning
confidence: 99%